Deaths related to Chagas disease and HIV/AIDS coinfection in Brazil: a nationwide population-based analysis. (9th December 2021) - Martins-Melo, Francisco Rogerlândio; Castro, Marcia C; Werneck, Guilherme Loureiro; Heukelbach, Jorg
Abstract: Background: Trypanosoma cruzi /HIV coinfection has been described as a relevant clinical event and an emerging public health problem. Here, we describe the epidemiological patterns of deaths related to Chagas disease and HIV/AIDS coinfection in Brazil from 2000 to 2019. Methods: We performed a nationwide population-based study using mortality data obtained from the Brazilian Mortality Information System. We included all deaths recorded in Brazil from 2000 to 2019 in which Chagas disease and HIV/AIDS were mentioned on the same death certificate, either as underlying or as associated causes of death. Results: Chagas disease and HIV/AIDS were mentioned on 196/22 663 092 death certificates. HIV/AIDS was the underlying cause in 58.2% (114/196) of deaths and Chagas disease in 33.2% (65/196). The average annual mortality rate was 0.05 deaths/1 000 000 inhabitants (95% CI 0.03 to 0.09). The highest death rates were found among males, those aged 60–69 y, Afro-Brazilians, those with 1–3 y of schooling/study and residents in Chagas disease-endemic regions/states. Respiratory, infectious/parasitic and cardiovascular diseases/disorders were the associated causes of death most commonly mentioned. Conclusions: Mortality due to Chagas disease and HIV/AIDS coinfection may be largely underestimated in Brazil. Our data further reinforce the importance of screening for T. cruzi infection in HIV-infected patients from Chagas disease-endemic areas. Appropriate clinical management should be ensured for Chagas disease and HIV coinfected patients.